Expository Teaching in Digital Spaces: A Case Study of the Adi Hidayat Official YouTube Channel - Pangesti, Zunita Lut Fiana; Zaini, Muhamad; Amalia, Rosyida (DINIKA : Academic Journal of Islamic Studies, 2025)
This research aims to explore the implementation of expository learning strategies on the YouTube channel "Adi Hidayat Official," which is a media platform utilized by Adi Hidayat. The research focuses on the forms of implementing expository learning strategies, audience feedback on Adi Hidayat's lectures, and the role of YouTube as an online expository learning medium. The research method employed is qualitative descriptive, utilizing data collection through desk review and observation. The implementation of expository strategies on the channel includes direct presentation, case studies, interaction with the congregation, organization through playlists, practical demonstrations, collaboration with guests, and the use of a whiteboard or flip chart. Audience feedback on Adi Hidayat's lectures tends to be positive and varied, encompassing prayers, material summaries, and timestamp stamps. YouTube's role as an expository learning medium on the "Adi Hidayat Official" channel involves broad accessibility, flexibility in time and location, a variety of topics and materials, and the creation of social interaction and a learning community.